Returning to the Pews: A Case Study of Mass Attendance Following the Second Wave of COVID-19 at St Paul the Apostle, Lyford Cay, The Bahamas - Fielding, William J. (International Journal of Bahamian Studies, 2024)
Following the start of the COVID-19 pandemic on the March 15, 2020, public worship was prohibited in The Bahamas on March 18, 2020. Using weekly Mass attendance figures at a Roman Catholic church serving western New Providence, The Bahamas for the period October 18, 2020 to June 11, 2023, this paper shows the steady rebound in the number of people attending Mass. Despite the stress and loss of life caused by COVID-19, the data indicate the willingness of worshippers to return to communal worship.